O caso da rabeca e do violino : a música armorial - COSTA, Luan Glauco Freire (2018)
The Armorial was an artistic movement founded in Recife in the years of 1970 and led by the writer and theatologist Ariano Suassuna. The pretension of the armorial artists was to create an authentically national erudite art from the popular Northeastern art, his works sought to approach vast artistic field: literature, engraving, sculpture and, among these, music. Music was the art of greatest evolution and importance within the armorial movement, having led to the creation of two distinct groups, namely: The Orchestra and the Armorial Quintet, born of the creative disagreements between Ariano Suassuna and Maestro Cussy de Almeida. It is precisely the creative disagreement between these two figures that gives breath to the present work: From the thought of the French sociologist Pierre Bourdieu, we seek to make the reading of the historical event constrained by the constitution of erudite armorial music as an exemplary case of the symbolic struggles that exist in the the core of the constitution of all erudite art. In addition, the aesthetic constitutions of the movement will be analyzed, guided by the previous Suassunian thought even to the official launch of the movement, the influences of the history of Brazilian music and its nationalism and the ideals of the regionalism of the sociologist from Pernambuco Gilberto Freyre.